Antiperlecan Antibodies Are Novel Accelerators of Immune‐Mediated Vascular Injury. Issue 4 (22nd February 2013) - Cardinal, H.; Dieudé, M.; Brassard, N.; Qi, S.; Patey, N.; Soulez, M.; Beillevaire, D.; Echeverry, F.; Daniel, C.; Durocher, Y.; Madore, F.; Hébert, M. J.
Abstract : Acute vascular rejection (AVR) is characterized by immune‐mediated vascular injury and heightened endothelial cell (EC) apoptosis. We reported previously that apoptotic ECs release a bioactive C‐terminal fragment of perlecan referred to as LG3. Here, we tested the possibility that LG3 behaves as a neoantigen, fuelling the production of anti‐LG3 antibodies of potential importance in regulating allograft vascular injury. We performed a case–control study in which we compared anti‐LG3 IgG titers in kidney transplant recipients with AVR (n = 15) versus those with acute tubulo‐interstitial rejection (ATIR) (n = 15) or stable graft function (n = 30). Patients who experienced AVR had elevated anti‐LG3 titers pre and posttransplantation compared to subjects with ATIR or stable graft function (p < 0.05 for both mediators). Elevated pretransplant anti‐LG3 titers (OR: 4.62, 95% CI: 1.08–19.72) and pretransplant donor‐specific antibodies (DSA) (OR 4.79, 95% CI: 1.03–22.19) were both independently associated with AVR. To address the functional role of anti‐LG3 antibodies in AVR, we turned to passive transfer of anti‐LG3 antibodies in an animal model of vascular rejection based on orthotopic aortic transplantation between fully MHC‐mismatched mice. Neointima formation, C4d deposition and allograft inflammation were significantly increased in recipients of an ischemic aortic allograft passively transferred with anti‐LG3 antibodies. Collectively, these data identify anti‐LG3 antibodies as novel accelerators of immune‐mediated vascular injury and obliterative remodeling. Abstract : This study shows that antibodies to LG3, a fragment of the vascular basement membrane molecule perlecan, are novel accelerators of immune‐mediated vascular injury and obliterative remodeling. See editorial by Nickerson and Rush on page 831.